Pengaruh Penambahan Infusa Daun Pandan Wangi (Pandanus amaryllifolius) dalam Air Minum terhadap Organ Hati, Jantung, Limpa dan Usus : The Effect of Adding Pandan Wangi Leaf Infusion (Pandanus amaryllifolius) in Drinking Water on the Liver, Heart, Spleen and Intestines - Sihombing, Sarah Nadia; Malvin, Toni; Fati, Nelzi; Nilawati, Nilawati (Fakultas Peternakan Universitas Jambi, 2024)
Background: Pandan wangi leaves (Pandanus amaryllifolius) contain bioactive compounds such as alkaloids, flavonoids and tannins which have antioxidant, antimicrobial and anti-inflammatory properties. Purpose: This study aims to determine the effect of adding pandan wangi leaf infusion to drinking water on the weight and percentage of liver, heart, spleen, intestine length and intestine weight of broilers. Methods: This research used 100 broiler chickens without sex separation which were randomly divided into 20 experimental units. Each experimental unit consisted of 5 chickens. Chickens were kept for 4 weeks, and data collection was carried out in week 4 at harvest. This research used a Completely Randomized Design (CRD) method with 4 treatments of pandan wangi leaf infusion in drinking water and with 5 replications. Each treatment was: P0: without adding pandan wangi leaf infusion, P1: adding 1% pandan wangi leaf infusion in water. drinking, P2: adding 2% pandan wangi leaf infusion to drinking water, and P3: adding 3% pandan wangi leaf infusion to drinking water. Results: The results showed that the treatment of adding pandan wangi leaf infusion to drinking water had a significant effect on spleen weight (P<0.05). The results of the study showed that the treatment of adding pandan wangi leaf infusion to drinking water had no significant effect (P>0.05) on liver, heart, intestine length and intestine weight of broilers. Conclusion: Based on the results of the research and discussion, it can be concluded that the physiological response of broilers to give pandan wangi leaf infusion in drinking water has a significant effect on spleen weight (P<0.05), but has no significant effect on liver, heart, intestine weight and intestine length (P> 0.05). The addition of pandan wangi leaf infusion up to 3% in drinking water can be tolerated on the weight of liver, heart, intestines and intestine length of broilers